Pengaruh Kepemimpinan, Stress Kerja, dan Kompensas Terhadap Kepuasan Kerja Karyawan pada PT. Jakarta Prima Cranes - Dian Novitasari,; Syahril Hasan,; Tutik Yuliani, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to determine the direct influence of leadership, job stress, and compensation variables on employee job satisfaction at PT. Jakarta Prima Cranes, Balikpapan. This research uses a sample of 40 respondents with a questionnaire data collection method and analysis tools using SPSS software. The results show that (1) Leadership has no significant effect on employee job satisfaction at PT. Jakarta Prima Cranes, Balikpapan; (2) Job stress has a negative and significant effect on employee job satisfaction at PT. Jakarta Prima Cranes, Balikpapan; (3) Compensation has a significant and positive effect on employee job satisfaction at PT. Jakarta Prima Cranes.